Role of the wife in the Jewish marriage in Old Testament Scripture, in Jewish law, and in Rabbinic literature - Da-Don, Kotel (Array, 2018)
The article is divided into three main sections: the first section analyzes the wife’s role in the Jewish marriage, as well as various questions which are inseparable from her status in Judaism, such as social life, equality, and polygamy. The second section deals with the institution of marriage in Judaism, the very wedding ceremony, and various practical questions which may arise during the wedding and later. These include issues such as the ketubah and divorce. In the last section of this article, the author seeks to present the Judaistic stance toward violence against women, especially towards beating up and raping, and he ends with the Judaistic view on how we should treat our wives. The author analyzes the aforementioned topics from the Old Testament Scripture, the Jewish law, and the Rabbinic literature from the days of Talmud until today. The author breaks down these questions based on a series of sources from the Rabbinic literature, from the days of Talmud, through the Middle Ages, all the way to the modern Rabbis, and the literature which has been translated into Croatian for the first time. The texts have been translated from Hebrew and Aramaic by the author himself.